Reperfusion status and postoperative blood pressure in acute stroke patients after endovascular treatment - Xu, Hongye; Li, He; Zhang, Ping; Gao, Yuan; Liu, Hanchen; Shen, Hongjian; Hua, Weilong; Zhang, Lei; Li, Zifu; Zhang, Yongxin; Xing, Pengfei; Zhang, Xiaoxi; et al. (Frontiers in Neurology, 2023)
Background and purpose An aggressive lowering of blood pressure (BP) could lead to neurological worsening, particularly of the area that has not been reperfused in acute stroke patients with large vessel occlusion (LVO). We sought to investigate the association of reperfusion status and BP course following mechanical thrombectomy (MT) with outcomes in LVO. Materials and methods Consecutive patients with LVO treated with MT between Jan 2020 to Jun 2021 were enrolled in a retrospective cohort study. Hourly systolic BP (SBP) and diastolic BP (DBP) were recorded for 72 h following MT and maximum SBP and DBP levels were identified. The Extended Thrombolysis in Cerebral Infarction (eTICI) scale was used to assess reperfusion extent. LVO patients were stratified in 2 groups based on reperfusion status: complete reperfusion (eTICI 3) and incomplete reperfusion (eTICI 2b/c). Three-month functional independence was defined as a modified Rankin Scale score of 0–2. Results A total of 263 acute ischemic stroke patients with LVO were retrospectively evaluated. Complete reperfusion was achieved in 210 patients (79.8%). Post-MT maximum SBP over 160 mmHg was significantly related to worse functional outcome (38.1% vs. 55.7%, p = 0.006), higher likelihood of in-hospital mortality and 3-month mortality (19.0% vs. 6.9%, p = 0.004, 27.4% vs. 14.3%, p = 0.012). No statistical correlation was found between reperfusion status and blood pressure level (p > 0.05). In patients with complete reperfusion, patients with an average BP 120-140 mmHg tends to have worse functional outcome compared with 100-120 mmHg (OR = 1.77, 95%CI: 0.97–3.23, p = 0.061). Conclusion High maximum SBP levels following MT are associated with an increased likelihood of 3-month functional dependence and mortality. An average BP of 100–120 mmHg tends to have better functional independence in completely reperfused patients. The effect of intensive BP control on incomplete reperfusion still warrants further investigations.